2007
DOI: 10.1364/oe.15.016376
|View full text |Cite
|
Sign up to set email alerts
|

Efficient waveguide-integrated tunnel junction detectors at 1.6 μm

Abstract: Near-infrared detectors based on metal-insulator-metal tunnel junctions integrated with planarized silicon nanowire waveguides are presented, which we believe to be the first of their kind. The junction is coupled to the waveguide via a thin-film metal antenna feeding a plasmonic travelling wave structure that includes the tunnel junction. These devices are inherently broadband; the design presented here operates throughout the 1500-1700 nm region. Careful design of the antenna and travelling wave region subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 28 publications
(28 reference statements)
0
44
2
Order By: Relevance
“…1B). Rectennas are traditionally used to generate power from microwaves (12), but have also been demonstrated for higher-frequency radiation, up to visible (12)(13)(14)(15)(16)(17)(18).…”
Section: Cooling Certain Electronic Degrees Of Freedommentioning
confidence: 99%
“…1B). Rectennas are traditionally used to generate power from microwaves (12), but have also been demonstrated for higher-frequency radiation, up to visible (12)(13)(14)(15)(16)(17)(18).…”
Section: Cooling Certain Electronic Degrees Of Freedommentioning
confidence: 99%
“…Conduction through the device is dominated by tunneling, and operation is relatively insensitive to temperature. Metal-insulator-metal (MIM) devices are of interest for hot electron transistors; 1,2 high speed diodes for rectenna based infrared (IR) energy harvesting, 3,4 IR detectors, 5 and thermal imaging; 6 selector diodes for resistive random access memory (RRAM); 7,8 tunneling cathodes; [9][10][11] and large area macroelectronics. 12,13 Figures of merit for MIM diodes include the asymmetry, nonlinearity, and turn-on voltage (V ON ).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7]14,16,18,19 We recently showed that roughness at the bottom metalinsulator interface can dominate the I-V behavior of MIM diodes and that the use of atomically smooth bottom electrodes combined with high quality insulators deposited via atomic layer deposition (ALD) allowed for fabrication of high quality MIM diodes with well controlled quantum mechanical tunneling. 20,21 Therefore, we fabricate M 1 IIM 2 diodes using smooth amorphous metal ZrCuAlNi (ZCAN) bottom electrodes 22 and nanolaminate insulator bilayers of HfO 2 and Al 2 O 3 deposited via ALD.…”
mentioning
confidence: 99%